DESAIN SISTEM MANAJEMEN BASIS DATA ASET TETAP PADA SEKOLAH HIGH SCOPE INDONESIA: Hengki Sikumbang - Jurnal, Redaksi Tim (PETIR, 2018)
The development of information technology does not only affect the business world , but also other areas , such as health , education , government and others. Advances in information technology , especially in the era of information also has implications for the management of fixed assets in an entity HighScope Indonesia School is one of the educational institutions from Playgroup through high school located in South Jakarta . Facilities, infrastructure , tools and equipment owned by the HighScope Indonesia School is a fixed asset that must be managed optimally in supporting the operational of education in school HighScope Indonesia. Management of fixed assets HighScope Indonesia School is still done manually , causing inefficient and ineffective in monitoring fixed assets . The purpose of this research is to create a design database management system fixed assets . System design by making the Data Flow Diagrams ( DFD ) and Entity Relationship Diagram ( ERD ). It is expected that the database management system can well explain all the activity so that desired results in accordance with the wishes of the user and is also expected to minimize the shortcomings and weaknesses of the current system.